Performance Characteristics of Parallel Slip Flow Microchannel Heat Exchanger - Hanoon, Hazim Abdulrazzaq; Alshara, Ahmed K. M. (Basrah Journal for Engineering Sciences, 2011)
Parallel flow microchannel heat exchanger performance was numerically investigated, for laminar, 3-D, incompressible and steady state flow with slip flow and temperature jump conditions. The continuity, Navier-Stokes equations and the energy equations for the hot and cold fluids were solved by using finite volumes method and SIMPLE algorithm method with FORTRAN code to obtain the velocity and temperature distributions for the two fluids and the separated wall between them. The main investigation parameter that affected on the performance and effectiveness of heat exchanger are: Reynolds number Re, thermal conductivity ratio Kr, Knudsen number Kn, thickness of separating wall, heat capacity ratio Cr and aspect ratio α. Increasing of Reynolds number, Knudsen number, thickness of separating wall, heat capacity ratio and aspect ratio each separately leads to decrease the effectiveness while increasing of thermal conductivity ratio up to 10 leads to increase the effectiveness. Also, it is found that friction number and Nusselt number both decreases with increasing Knudsen number.